2015
DOI: 10.1016/j.rboe.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anterolateral ligament of the knee by means of magnetic resonance examination

Abstract: ObjectiveTo evaluate the presence of the anterolateral ligament (ALL) of the knee in magnetic resonance imaging (MRI) examinations.MethodsThirty-three MRI examinations on patients’ knees that were done because of indications unrelated to ligament instability or trauma were evaluated. T1-weighted images in the sagittal plane and T2-weighted images with fat saturation in the axial, sagittal and coronal planes were obtained. The images were evaluated by two radiologists with experience of musculoskeletal patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
59
4
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 13 publications
3
59
4
2
Order By: Relevance
“…On dissection, an anterolateral structure was identified in eight of ten knees-within the reported range of ALL prevalence [4,5,8,15,19]. The structure did not appear to be contiguous with the meniscofemoral ligament in any samples.…”
Section: Discussionmentioning
confidence: 96%
“…On dissection, an anterolateral structure was identified in eight of ten knees-within the reported range of ALL prevalence [4,5,8,15,19]. The structure did not appear to be contiguous with the meniscofemoral ligament in any samples.…”
Section: Discussionmentioning
confidence: 96%
“…The small ALL thickness and its anatomical variability also difficult the complete visualization. 5,11,12 Helito et al 5 performed a study in 39 patients and identified the ALL in its entirety in around two-thirds of the MRI scans, but additional coronal proton densityeweighted sequences without fat saturation were also used. Taneja et al, 13 in a study of 70 patients, were able to visualize the ALL in its entirety in a very low percentage of the MRI scans, observing some portion of the ligament in around half of the scans.…”
Section: Discussionmentioning
confidence: 99%
“…Coquart et al [11] reported completely visible in 82% and partially visible in 11.5%. Helito et al [18] reported completely visible in 33.3% and partially visible in 48.5%. A recent study reported that the percentage agreement between MRI and surgical ndings was 88% for ALL injury.…”
Section: Discussionmentioning
confidence: 94%